The efficacy and safety of keverprazan, a novel potassium‐competitive acid blocker, in treating erosive oesophagitis: a phase III, randomised, double‐blind multicentre study. Issue 12 (3rd May 2022) - Chen, Songfeng; Liu, Deliang; Chen, Honghui; Liao, Aijun; Li, Fangfang; Liu, Chengxia; Li, Xing; Li, Shengbao; Zhang, Yan; Wang, Yang; Xia, Min; Guo, Qinghong; et al.
Summary: Background: Keverprazan is a novel potassium‐competitive acid blocker (P‐CAB) with a strong acid‐suppressive capacity that may provide clinical benefit in acid‐related diseases. Aims: This study aimed to explore the non‐inferior efficacy and safety of keverprazan to lansoprazole in treating erosive oesophagitis (EO). Methods: This was a phase III, randomised, double‐blind multicentre study. Patients were randomised to receive keverprazan 20 mg once daily or lansoprazole 30 mg once daily for 4–8 weeks. EO healing rates and adverse events (AEs) were compared between the keverprazan group and the lansoprazole group. Results: A total of 238 patients comprised the full analysis set (FAS) while 221 patients comprised the per‐protocol set (PPS). For FAS analysis, the EO healing rates at week 8 were 95.8% (114/119) and 89.9% (107/119) for keverprazan and lansoprazole respectively. For PPS analysis, the EO healing rates at week 8 were 99.1% (110/111) and 92.7% (102/110) for keverprazan and lansoprazole respectively. Non‐inferiority of keverprazan compared with lansoprazole according to EO healing rates at 8 weeks was demonstrated in both FAS (difference: 5.8% [95% CI: −0.6% to 12.3%]; p = 0.081) and PPS (difference: 6.1% [95% CI: 1.1%–11.2%]; p = 0.018) analysis. Drug‐related AEs were reported in 34.5% (41/119) patients of the keverprazan group and 25.2% (30/119) patients of the lansoprazole group with no significant difference ( p = 0.156). No severe AE happened in the keverprazan group. Conclusions: This study demonstrated the non‐inferior efficacy of keverprazan to lansoprazole in treating EO. The incidences of drug‐related AEs were comparable between keverprazan and lansoprazole. Abstract : The current multicentre study demonstrated the non‐inferior efficacy of keverprazan to lansoprazole in treating erosive oesophagitis. The incidences of drug‐related adverse events were comparable between keverprazan and lansoprazole.